Soil, Vegetation and Parent Material Relationship in Maldeota Area of Mussoorie forest Division, Uttarakhand - Tewari, Rachna (Indian Forester, 2007)
Interrelationship of soil, vegetation and geology was studied in Maldeota area of Mussoorie Forest Division, Uttarakhand (altitude 750 to 1,050 m above msl). The physical and chemical properties of the soils under different vegetative covers were related to various vegetational parameters and parent materials. The results showed that range in pH was from 6.0 to 8.2 while water holding capacity varied from 28.9 to 60.7. Organic matter content was generally high with maximum accumulation in the surface horizon. Cation exchange capacity of the soils varies from 2.9 to 30.1 cmol. (p+) kg-1. Elluviation and illuviation processes were well marked in most pedons, which results in horizon distinction.